2013
DOI: 10.1148/radiol.12121114
|View full text |Cite|
|
Sign up to set email alerts
|

Pulmonary Intersegmental Planes: Imaging Appearance and Possible Reasons Leading to Their Visualization

Abstract: Purpose:To describe the normal imaging appearance of pulmonary intersegmental planes on thoracic computed tomographic (CT) scans and determine the possible reasons related to their visualization in terms of aging and anatomy. Materials and Methods:The study was approved by the internal ethics review board. Informed consent was obtained. A retrospective review was undertaken of 104 thoracic multidetector CT scans of an older group (.65 years) and younger group (,55 years). The number, location, and appearance r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The linear shadow connecting the pulmonary segmental arteries to the horizontal fissure in this study has been mentioned in some literatures, but no in-depth study is conducted. [ 2 , 3 ] To the best of our knowledge, this is the first systematic analysis for the linear shadow connecting the pulmonary segmental arteries to the horizontal fissure. According to the study, we observe that: first, the linear shadow is observed in 54.33% of normal lung CT images without correlation with gender, age, and smoking history, but with correlating to the integrity of the horizontal fissure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The linear shadow connecting the pulmonary segmental arteries to the horizontal fissure in this study has been mentioned in some literatures, but no in-depth study is conducted. [ 2 , 3 ] To the best of our knowledge, this is the first systematic analysis for the linear shadow connecting the pulmonary segmental arteries to the horizontal fissure. According to the study, we observe that: first, the linear shadow is observed in 54.33% of normal lung CT images without correlation with gender, age, and smoking history, but with correlating to the integrity of the horizontal fissure.…”
Section: Discussionmentioning
confidence: 99%
“…Although linear shadows are intrinsic to the lungs, it is still necessary to identify similar normal and abnormal structures in the lungs on thin-slice CT, such as interlobular septum, segmental septum, pulmonary ligament, fibrous cords, and etc. [ 2 , 10 ] First, the interlobular septa are formed by the inward recession of the visceral pleura, which cannot be seen in normal circumstances unless the interstitium of the interlobular septa are thickened. The interlobular septa are perpendicular to the pleura with the length of about 10 to 25 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Zuo et al. ), and demonstrated that the intersegmental septa can be seen as lines with hyper‐attenuation on multi‐slice computed tomography (MSCT). The high density on MSCT scans of the intersegmental septum indicated the existence of local interstitial fluid.…”
Section: Discussionmentioning
confidence: 99%
“…; Zuo et al. ), and its composition is only visible in H&E sections at low magnification (Berkmen et al. ).…”
Section: Introductionmentioning
confidence: 99%